Internal Rhyme - From the Arabic Rhetoric To the Modern Criticism - Abbas Mohammed Al. Aboudi, Maha; خلباص حمادي, إسماعيل (Journal of College of Education, 2020)
The linguists have realized many techniques of rhythm, which is called today's internal rhythm, but this realization was in the field of eloquence, as the Arabic scholars were interested in studying vocabulary and then sentences, and they were interested in the occurrence of some linguistic phenomena that have artistic connotations, and extended their research to variations in composition based on the number of Of the influences worthy of consideration, and the splendor of the rhythm and its attractiveness is what these words possess from the rhythm of a musical sound of accuracy and harmony, because rhythm is the spirit of music and its pulsating heart expressing the feelings of feelings, and a realistic translation of the poet's emotions and desires and what he conflicts with himself, and the rhythm Different forms are generated with each change, adaptation and crystallization subject to the poetic language and try to exploit them in accordance with the requirements of expression.
Keywords: the inner rhythm of the prose poem, vocal, linguistic, semantic, and white